(3QhSjG hdYHI GdgjefI Ydi GdWGbI (B:s ((3QDjI aj GdCOhGQ hGdGSJQGJjLjGJ(B) /s - (3GdNaGLj, eMeO LGSe MSjfs ((3YeGf (B[(3GdCQOf(B] :s (3OGQ CeLO ddfTQ hGdJhRjY (B:s (3EHUGQ fGTQhf hehRYhf,s, 2019)
(3JTZd eUGOQ GdWGbI CgejI eJYGXeI dOi GdOhd GdUfGYjI GdcHQi, djS chfgG TQjGf GdMjGI GdGbJUGOjI hGdSjGSjI hGdYScQjI aMSH, Hd dCgejJgG aj JMOjO bhI GdOhdI hhVYgG GdYGdej, hdG SjeG eY hLhO Ndd aj gjcd JhRjY eUGOQ GdWGbI, hYdj VhA Pdc jbOe gPG GdcJGH OQGSI HYfhGf, QhSjG hdYHI GdgjefI Ydi GdWGbI, hJbY GdOQGSI aj KdGKI aUhd (B: ((3GdEWGQ GdfXQj ddOQGSI, CgejI GdWGbI aj GdESJQGJjLjI GdQhSjI GdTGedI, hGdeJZjQGJ GdOhdjI hCKQgG aj GdGSJQGJjLjI GdQhSjI JLGg GdGJMGO GdChQHj(B)s
(3HHdjhLQGajI (B: (3UaMI (B195-220.s
Keywords: (3GdWGbIs -- (3LhGfH SjGSjIs -- (3QhSjGs; (3QhSjGs -- (3YdGbGJ NGQLjIs; (3QhSjGs -- (3SjGSI hMcheIs